2015
DOI: 10.1016/j.dnarep.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

The steady-state level and stability of TLS polymerase eta are cell cycle dependent in the yeast S. cerevisiae

Abstract: Polymerase eta (Pol eta) is a ubiquitous translesion DNA polymerase that is capable of bypassing UV-induced pyrimidine dimers in an error-free manner. However, this specialized polymerase is error prone when synthesizing through an undamaged DNA template. In Saccharomyces cerevisiae, both depletion and overproduction of Pol eta result in mutator phenotypes. Therefore, regulation of the cellular abundance of this enzyme is of particular interest. However, based on the investigation of variously tagged forms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…The D. melanogaster homolog of TRIP, NOPO, is known to assemble K63-linked chains, possibly indicating a regulatory function of TRIP-mediated polymerase η modification as well, and interactions of both TRIP and NOPO with several Y-family polymerases suggest a conservation of the process ( Wallace et al, 2014 ). In budding yeast, polymerase η has been found to be ubiquitylated as well; however, the effects of this modification on protein stability remain controversial ( Parker et al, 2007 ; Skoneczna et al, 2007 ; Pabla et al, 2008 ; Plachta et al, 2015 ). Ubiquitin-mediated proteolysis also controls the levels of budding yeast TLS polymerase Rev1 along the cell cycle, thus limiting the bulk of its mutagenic activity to the G2/M phase ( Waters and Walker, 2006 ).…”
Section: Ubiquitin and Sumo In Dna Replication Stressmentioning
confidence: 99%
“…The D. melanogaster homolog of TRIP, NOPO, is known to assemble K63-linked chains, possibly indicating a regulatory function of TRIP-mediated polymerase η modification as well, and interactions of both TRIP and NOPO with several Y-family polymerases suggest a conservation of the process ( Wallace et al, 2014 ). In budding yeast, polymerase η has been found to be ubiquitylated as well; however, the effects of this modification on protein stability remain controversial ( Parker et al, 2007 ; Skoneczna et al, 2007 ; Pabla et al, 2008 ; Plachta et al, 2015 ). Ubiquitin-mediated proteolysis also controls the levels of budding yeast TLS polymerase Rev1 along the cell cycle, thus limiting the bulk of its mutagenic activity to the G2/M phase ( Waters and Walker, 2006 ).…”
Section: Ubiquitin and Sumo In Dna Replication Stressmentioning
confidence: 99%
“…Previous findings that the TLS polymerases Pol eta and Rev1 are regulated in the cell cycle under stress-free conditions (Waters and Walker 2006;Plachta et al 2015) prompted us to further investigate the regulation of these polymerases in response to DNA damage. Since it has previously been shown that tagging of Pol eta with various epitopes differently affects the stability of this polymerase (Plachta et al 2015), we analyzed the levels of the native form of Pol eta in the current study. On the other hand, we studied the levels of a Rev1-ProA fusion protein, as an assay for immunodetection of the native form of Rev1 in yeast extracts has not yet been developed.…”
Section: Uv Irradiation Affects the Cellular Abundance Of Y-family Pomentioning
confidence: 99%
“…The band intensities were normalized to the intensities of the respective Pgk1 bands and to intensities at time 0′. b, e, h, k FACS data were used to monitor S-phase progression in cells arrested in G1-phase of the cell cycle (Plachta et al 2015;Waters and Walker 2006). Our results indicated that the levels of these proteins did not significantly increased when cells arrested with α factor in G1-phase were treated with UV radiation (10, 50, or 80 J/m 2 ) ( Fig.…”
Section: Uv Irradiation Affects the Cellular Abundance Of Y-family Pomentioning
confidence: 99%
“…For example, both Rad30 (the S. cerevisiae homologue of POL-η) and Rev1 undergo cell cycle-dependent proteolysis to limit mutagenic activity, and in the case of Rad30, this is mediated via the SCF ubiquitin ligase with the F-box protein Ufo1 (Waters and Walker 2006; Skoneczna et al 2007; Plachta et al 2015). The second, and perhaps more important, mechanism restraining TLS activity is mediated through deubiquitylation of monoubiquitylated PCNA via the USP1 isopeptidase (Huang et al 2006).…”
Section: 7 Regulation Of Dna Synthesis Via the Upsmentioning
confidence: 99%